2000
DOI: 10.1046/j.1365-2044.2000.01205.x
|View full text |Cite
|
Sign up to set email alerts
|

Airway obstruction with cricoid pressure

Abstract: SummaryCricoid pressure may cause airway obstruction. We investigated whether this is related to the force applied and to the technique of application. We recorded expired tidal volumes and inflation pressures during ventilation via a facemask and oral airway in 52 female patients who were anaesthetised and about to undergo elective surgery. An inspired tidal volume of 900 ml was delivered using a ventilator. Ventilation was assessed under five different conditions: no cricoid pressure, backwards cricoid press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
103
0
6

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(109 citation statements)
references
References 22 publications
0
103
0
6
Order By: Relevance
“…Its use has also been associated with serious complications including distorted laryngeal view, increased difficulty with intubation, laryngeal trauma, cricoid fracture, and esophageal rupture. [11][12][13][14][15] To date, there has never been a randomized, controlled study assessing the effectiveness of CP. Schreiner has pointed out the difficulty of conducting such a study given the low event rates for regurgitation and pulmonary aspiration.…”
Section: Objectifmentioning
confidence: 99%
“…Its use has also been associated with serious complications including distorted laryngeal view, increased difficulty with intubation, laryngeal trauma, cricoid fracture, and esophageal rupture. [11][12][13][14][15] To date, there has never been a randomized, controlled study assessing the effectiveness of CP. Schreiner has pointed out the difficulty of conducting such a study given the low event rates for regurgitation and pulmonary aspiration.…”
Section: Objectifmentioning
confidence: 99%
“…In the event of a 'cannot intubate' scenario, the manual face mask ventilation of the lungs with oxygen with continued CP application is an imperative (13). We found that CP significantly hampered BMV compared to no CP (41.7% vs. 98.3%, respectively).…”
Section: Discussionmentioning
confidence: 80%
“…Previous studies confirm impairment of ventilation via the classic LMA, when CP was applied prior to device insertion (12,14,15). Application of CP may cause laryngeal obstruction due to cricoid cartilage deformation or tilting resulting in a vocal cord closure (13). Tilting of the cricoid cartilage resulting in airway obstruction is more likely to occur with classic LMA placement, as its tip lies behind the upper part of the cricoid (16).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…There is also conflicting evidence regarding the effect of cricoid pressure (CP) on the laryngoscopic view with the conventional Macintosh laryngoscope. [6][7][8][9][10] The Truview Evo2 TM blade (Truphatek Holdings Ltd, Netanya, Israel) enables an indirect view of the vocal cords and may improve glottic visualization compared with the conventional Macintosh laryngoscope. 11,12 The Truview Evo2 blade, based on a combination of an optical system with a steel blade, provides a 42°angled view (refracted) through a 15-mm eyepiece.…”
Section: Résumémentioning
confidence: 99%